Psychometric Properties of The Irrational Beliefs Scale for Insomnia (IBSI) In Turkish Emerging Adults - Kabadayı, Fedai; Kılıç, Sabire; Yazıcı-Kabadayı, Sema (Anales de Psicología / Annals of Psychology, 2024)
The present study aimed to assess the psychometric properties of the Irrational Beliefs Scale for Insomnia (IBSI) in Turkish emerging adults. The measurement instrument aims to assess irrational beliefs by measuring four core irrational beliefs (demandingness, awfulizing, frustration intolerance, and global evolution of worth). A total of 762 emerging adults (556 female, 206 male) between the ages of 19 and 28 were included in all stages of the study. The results indicated that the IBSI, consisting of 4 dimensions and 24 items, is valid and reliable according to the results of EFA, CFA, and network analysis. The calculated Cronbach's α and McDonald's ω showed that the instrument was satisfactory. The results provide strong evidence that the IBSI is a valid and reliable instrument for Turkish emerging adults.